Compaq Computer Corporation. - Ahmed, Reem Saaldeldin (2004)
Compaq Computer Corporatin is a leading global provider of enterprise technology and solutions. Compaq designs, develops, manufactures and markets hardware and software, solutions and services, including industry-leading enterprise computing solutions, fault tolerant business-critical solutions, communications products, and desktop portable personal computers that sold over 200 countries.